The Effect of Corporate Social Responsibility on Tax Aggressiveness and Profitability as a Moderating Variable - Saputra, Rianda; Iskandar (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
The purpose of this study is to find out and analyze the influence of Corporate Social on Responsibility on Tax Aggressiveness and to find out the influence of professionalism in moderating the relationship between Corporate Social Responsibility and Tax Aggressiveness. The sample was determined using the purposive sampling method with a total of 7 companies as the research sample. The data analysis tool used is the SPSS version 28 program. The results of this study show that Corporate Social Responsibility has a significant and negative effect on tax aggressiveness and profitability as a moderation variable cannot moderate the influence of Corporate Social Responsibility on tax aggressiveness